2014
DOI: 10.4088/jcp.13m08879
|View full text |Cite
|
Sign up to set email alerts
|

Method of Suicide Attempt and Reaction to Survival as Predictors of Repeat Suicide Attempts

Abstract: Assessment of the patient's reaction to survival, regardless of method of attempt, is important to identify risk of repeat attempts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Given known difficulties with help-seeking among suicidal individuals (Downs & Eisenberg, 2012;Hawton, Saunders & O'Connor, 2012), any research that demonstrates the effectiveness of a therapeutic intervention may be beneficial to the client, to those in their immediate support network and to the therapist. For the client, research has demonstrated the high degree of ambivalence among those with suicidal ideation (Bhaskaran et al, 2014;O'Connor et al, 2012). Any potential hope instilled by evidence of recovery and of an increased positive and decreased negative outlook, therefore, may be the impetus necessary to engage in therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given known difficulties with help-seeking among suicidal individuals (Downs & Eisenberg, 2012;Hawton, Saunders & O'Connor, 2012), any research that demonstrates the effectiveness of a therapeutic intervention may be beneficial to the client, to those in their immediate support network and to the therapist. For the client, research has demonstrated the high degree of ambivalence among those with suicidal ideation (Bhaskaran et al, 2014;O'Connor et al, 2012). Any potential hope instilled by evidence of recovery and of an increased positive and decreased negative outlook, therefore, may be the impetus necessary to engage in therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the lifetime prevalence and type (cutting vs. other) of non-suicidal self-injuries was considered. [35][36][37] -Previous SA characteristics: the lifetime prevalence of SA (including the SA that motivated the present emergency visit) and the method used in the most recent SA were classified according to the literature as drug overdose, defenestration, hanging, suffocation, poisoning and phlebotomy, 12,23 after aggregation into the categories drug overdose and other. -Prior psychiatric treatment and use of psychiatric services in the past 5 years 10 included psychiatric consultations, hospital admissions (number of episodes: 0, 1, 2, X 3), time since the last episode (o 1 year or X 1 year), and visits to the psychiatric ER (0, 1, 2 or X 3, excluding the present emergency visit).…”
Section: Variablesmentioning
confidence: 99%
“… 22 The repeated SA rate seems to be especially high during the first 6 months after a SA 8 : this is considered the highest risk period for repeated SA, with rates of up to 9%. 23 However, SA rates can reach 60% within 1-2 years. 24 Comparatively, the completed suicide rate is approximately 3% in 1-4 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…33,34,[70][71][72] This study has several potential limitations. First, data were not available concerning several clinically important factors, such as patients' reactions to surviving self-harm, 73 self-harm intent, 23 Without more detailed information on whether the self-harm occurred with or without a suicidal intent, it is impossible to exclude the possibility that some discharged patients were at relatively low risk, although deliberate self-harm is a main risk factor for fatal and nonfatal suicide attempts, 2,3 particularly among older adults. 10 Second, concerns exist over the validity and completeness of ICD codes to measure self-harm.…”
Section: Outpatient Mental Health Carementioning
confidence: 99%
“…Prior US research shows that roughly 50% of younger ED patients discharged to the community following self-harm proceed to followup on referrals to outpatient mental health services 26,28,62. First, data were not available concerning several clinically important factors, such as patients' reactions to surviving self-harm,73 self-harm intent,23 or the extent to which patients were offered referrals for outpatient mental health care, all of which may influence hospital admission, recognition of mental disorders, or use of follow-up outpatient mental health care. Moreover, the only variable associated with lower likelihood of follow-up mental health care was male gender (ARR = 0.82, 99% CI = 0.71-0.94), which is consistent with research demonstrating lower help-seeking behavior in men 66,67.…”
mentioning
confidence: 99%